Driveline oscillations damping: A tractable predictive control solution based on a piecewise affine model. (February 2016) - Caruntu, Constantin F.; Balau, Andreea E.; Lazar, Mircea; Bosch, Paul P.J.v.d.; Di Cairano, Stefano
Abstract: This paper deals with the problem of damping driveline oscillations, which is crucial to improving driveability and passenger comfort. Recently, this problem has received an increased interest due to the introduction in several production vehicles of the dual-clutch powershift automatic transmission with dry clutches. This type of transmission improves fuel economy, but it results in a challenging control problem, due to driveline oscillations. These oscillations, also called "shuffles", occur during gear-shift, while traversing backlash or when tip-in and tip-out maneuvers are performed. The contribution of this paper is to demonstrate that horizon-1 model predictive control based on flexible Lyapunov functions and piecewise affine drivetrain models with three inertias provides an effective solution to driveline oscillation damping. Several simulations based on realistic scenarios show that the proposed control scheme can handle both the performance and physical constraints, and the strict limitations on the computational complexity. Highlights: We derive an accurate piecewise affine drivetrain model. We design a horizon-1 MPC strategy to minimize the drivetrain oscillations. A flexible Lyapunov function is employed to obtain a stability guarantee. The controller has the potential to meet the real-time control specifications.